ETHNOFORESTRY AS A PILLAR OF SOCIAL AND ECOLOGICAL RESILIENCE IN TROPICAL FORESTS - Villanueva, Andres; Li, Catherine; Fernandez, Carlos (Journal of Selvicoltura Asean, 2026)
Tropical forests are critical to global biodiversity and climate regulation. However, they face increasing threats from deforestation, climate change, and unsustainable land use practices. Ethnoforestry, the integration of indigenous knowledge and forest management practices, has emerged as a crucial component of both ecological and social resilience. Indigenous communities have long managed tropical forests using sustainable practices that ensure the balance of ecosystems while supporting local livelihoods. This research explores the role of ethnoforestry as a pillar of resilience in tropical forest regions. This study aims to investigate how ethnoforestry practices contribute to social and ecological resilience in tropical forests. Specifically, it seeks to understand the mechanisms through which indigenous forest management practices help mitigate environmental degradation and enhance community well-being. A qualitative approach was used, including field observations, interviews with indigenous forest managers, and analysis of case studies from tropical forest regions in Southeast Asia and Latin America. Data were analyzed using thematic analysis to identify key practices that promote resilience. The findings highlight that ethnoforestry practices, such as agroforestry, selective logging, and forest regeneration, contribute significantly to both biodiversity conservation and social cohesion. These practices foster sustainable resource use, mitigate environmental degradation, and enhance the adaptive capacity of communities. Ethnoforestry plays a vital role in enhancing the resilience of both ecosystems and human communities in tropical forests. Integrating indigenous knowledge into forest management strategies is essential for achieving long-term sustainability.